Estimation of Impact Loads in a Hydraulic Breaker by Transfer Path Analysis - Changheon Song; Dae Ji Kim; Jintai Chung; Kang Won Lee; Sang Seuk Kweon; Young Ky Kang (Shock and Vibration)
The aim of this study is to estimate the impact loads delivered to the housing of a hydraulic breaker quantitatively. Striking forces caused vibrations in the equipment housing, which were experimentally measured, and frequency response functions were also found through modal impact experiments. Transfer path analysis (TPA) method of the data quantified the impact loads delivered to the housing. TPA method can analyze the relationship between the vibration energy and the transfer path of an excitation source and so explore the way in which vibrations on each path contribute to the entire vibration profile. The impact loads of each part derived by TPA method were compared with the impact loads in the chisel derived from strain gauge measurements of the striking energy. This comparison validated the TPA approach. This study describes the basic concepts and components of TPA method and also reviews its applicability to mechanical equipment that experiences impact vibrations and impact loads.